German Paths to Experience - Favaretti Camposampiero, Matteo (Con-Textos Kantianos. International Journal of Philosophy, 2022)
Review of: Karin de Boer and Tinca Prunea-Bretonnet (eds.), The Experiential Turn in Eighteenth-Century German Philosophy, New York and London, Routledge, 2021, xii+309 pp. ISBN: 978-1-138-60683-8.